Genetic variability and phylogenetic relationships of Begonia multangula based on atpB-rbcL non-coding spacer of cpDNA sequences - TRI WARSENO; MUHAMMAD EFENDI; ABDUL RAZAQ CHASANI; BUDI SETIADI DARYONO (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Warseno T, Efendi M, Chasani AR, Daryono BS. 2022. Genetic variability and phylogenetic relationships of Begonia multangula based on atpB-rbcL non-coding spacer of cpDNA sequences. Biodiversitas 23: 5491-5501. Begonia (Begoniaceae) belongs to Section Platycentrum-Sphenanthera Group which has a wide distribution from Sumatra to the Lesser Sunda Islands and Sulawesi. Information on B. multangula genetic variability and intraspecies relationships based on molecular characters is critical for developing appropriate strategies in conservation biology, breeding activities, and many other applied fields. The genetic variability and interspecific relationships of B. multangula in Indonesia were investigated using sequence data from the atpB-rbcL intergenic spacer (IGS) cpDNA regions. The atpB-rbcL IGS fragment was amplified using atpB-1 as the forward primer and rbcL-1 as the reversed primer. Genetic variations were found in the length of the sequence and nucleotide divergences in the atpB-rbcL IGS region. The genetic distance between 822 fixed sites ranged from 0 to 0.61%. Eighteen of the 822 sites (99.27%) analyzed were invariable, six sites (0,73%) were variable consisting of 4 singleton variable sites and two parsimony informative sites, and twelve sites were gaps. The phylogenetic relationships generated by B. multangula based on the atpB-rbcL IGS sequence analysis indicated the genetic variation and divided it into two clades. However, the clustering pattern of B. multangula specimens resulting from molecular analysis based on atpB-rbcL IGS sequences did not show the geographic clustering grouping pattern.